The Impact Of Brand Interactivity And Involvement, Moderated By Social Media Engagement, On Brand Trust, Self-Brand Connection, And Loyalty In Indonesian Online Education Platforms - Nuha Adinata (Eduvest - Journal of Universal Studies, 2025)
Despite the rapid growth of online education platforms in Indonesia, challenges surrounding user loyalty and brand trust remain critical. This study examines the influence of brand interactivity and brand involvement on brand loyalty, mediated by social media customer brand engagement (CBE), self-brand connection, and brand trust. Utilizing a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, the study surveyed 296 respondents aged 16–24 who had used online education platforms in the past year. The findings reveal that both brand interactivity and brand involvement significantly impact CBE. Furthermore, CBE acts as a strong mediator in the relationship between brand interactivity and brand involvement with brand trust, self-brand connection, and brand loyalty. CBE also has a direct influence on brand trust, self-brand connection, and brand loyalty. In addition, both brand trust and self-brand connection positively influence brand loyalty. These findings offer theoretical contributions to understanding brand engagement dynamics on social media and strategic implications for the online education industry to foster user loyalty by enhancing interactivity and emotional connection with the brand.